Industrial traumatism and occupational morbidity in mining industry of Kazakhstan - Nurbek Yerdessov; Asset Izdenov; Timur Beisenov; Roza Suleimenova; Bakhtiyar Serik; Ermek Sraubaev (SAGE Publishing, 2021)
This article presents data in the dynamics on industrial injuries and occupational morbidity in the mining industry of the Republic of Kazakhstan. The aim of this study is to analyze occupational injuries and occupational diseases between 2008 and 2018. An analysis of the number of victims of accidents, including those who died from accidents at work during the period, shows indicators of occupational injuries in the gender aspect, the outcome of accidents by degrees of severity and the material consequences of accidents. During the analyzed period, the overall level of occupational injuries and occupational morbidity in the country remains high. The material consequences of accidents, in addition to social damage, bring great material losses to the state.